Communicating in/from the Cave: a communication for development/social change project aimed at enhancing communication, action and learning within the science cave, a learner-led Grade 10 science club in a public school in Makhanda - Bombi, Thandi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
This research seeks to design, execute and reflect on a process where the principles and techniques of Communication for Development and Social Change are applied to enhance, support and develop qualitative changes within a learner-led Grade 10 science club at a public school in Makhanda. It draws and reflects on an ethnographic action research (Tacchi et al 2003) cycle proposed to explore the club's communicative ecology (Foth & Hearn 2007) and resources, and understand how these have the potential to encourage the expression of voice (Couldry 2010: 580) and participation (Carpentier, 2011) in the members of the club. The research then attempts to understand the kind of communication, action and learning that takes place as well as the ways in which the framework is able to support the club (or not). The research uses an ethnographic narrative, told from the perspective of the researcher informed by field notes, interviews and participant reflections written during the intervention. This narrative, alongside an analytical summery of the club's complex communicative ecology, tells the story of a club building confidence within a closed group and using that to connect with a wider public, articulating its needs, resources and potential supporting stakeholders for the club's future development. The club is able to share its achievements with a community of peers and uses the platform of Facebook, to communicate with and inspire other like-minded people with an interest in science and their community.
Keywords: Science -- Study and teaching (Secondary) -- South Africa; Communication in science -- South Africa; Science -- Study and teaching (Secondary) -- South Africa -- Makhanda; Communication in science -- South Africa -- Makhanda; Student centered learning -- South Africa; Student centered learning-- -- South Africa -- Makhanda